IMPLEMENTING TASK-BASED LANGUAGE TEACHING TO OVERCOME THE PROBLEMS OF TEACHING SPEAKING - SUSWATI HENDRIANI (Ta'dib, 2014)
Teaching students  to speak English is not an easy task. The teachers shoud consider and think hard about several points to be done: to  make the students motivated to speak English, to keepthem speaking the new language, and to make them have accuracy in speaking the language, and  to correct the students’ mistakes without feeling being  blamed or discouraged. To handle the difficult  tasks previously mentioned, the English teachers should find a solution. Teaching the students through unforgettable, interesting experiences might be one of the solutions that they can choose. Therefore, teaching speaking might be best done through task-based instruction. Kata kunci: teaching, speaking